Ecosystem impacts of folivory and frugivory by Japanese macaques in two temperate forests in Yakushima. Issue 6 (24th December 2013) - Hanya, Goro; Fuse, Mieko; Aiba, Shin‐Ichiro; Takafumi, Hino; Tsujino, Riyou; Agetsuma, Naoki; Chapman, Colin A.
<x xml:space="preserve">Abstract</x> Comparing animal consumption to plant primary production provides a means of assessing an animal's impact on the ecosystem and an evaluation of resource limitation. Here, we compared annual fruit and leaf consumption by Japanese macaques (Macaca fuscata) relative to the annual production of these foods in the lowlands and highlands of Yakushima Island, Japan. We estimated consumption by macaques by the direct observation of macaque groups for 1 year in each habitat. We estimated leaf production as the sum of leaf litter fall (corrected for the effect of translocated organic and inorganic matter) and folivory by insects (assumed to be 10%) and by macaques. We estimated fruit production as the sum of fruit litter fall and consumption by birds (estimated by the seed fall) and macaques. The impact of macaque folivory at the community level was negligible relative to production (∼0.04%) compared with folivory by insects (assumed to be 10%); however, for some species, macaque folivory reached up to 10.1% of production. Tree species on which macaques fed did not decline in abundance over 13 years, suggesting that their folivory did not influence tree species dynamics. For the three major fleshy‐fruited species in the highland site, macaques consumed a considerable portion of total fruit production (6–40%), rivaling the consumption by birds (32–75%). We conclude that at the community level, macaque folivory was negligible compared with the leaf production, but frugivory was not. Am. J. Primatol. 76:596–607, 2014. © 2013 Wiley Periodicals, Inc.